Politik Sophismata: Analisis Sosiologi Sastra Terhadap Novel Sophismata Karya Alanda Kariza - Maulida, Aulia (LoroNG: Media Pengkajian Sosial Budaya, 2018)
This research aims to reveal two sides of political understanding in the novel Sophismata by Alanda Kariza based on the models of political behavior in individual units of political actors. This research is a qualitative research that uses the sociological approach. The novel Sophismata is the primary data source, while a variety of literature on the sociology approach to literature is the secondary data source. The data collection technique used is the technique of reading and note-taking. While for the analysis of results using the spiral analysis technique by Creswell with steps: data management, reading and memoing, classification and interpretation, then data visualization. As for the results of this research, it was found that: the three main figures in the novel Sohpismata describe the models of political behavior in individual units of political actors. Namely figure Johar Sancoyo described political actors (leaders), figure Timur described political activists and figure Sigi described ordinary citizens. In addition, there were also differences in understanding of politics, for Johar and Timur, politics spoke of common interests while for Sigi, politics spoke of personal interests wrapped in mutual interests. Penelitian ini bertujuan untuk mengungkapkan dua sisi pemahaman dunia politik dalam novel Sophismata karya Alanda Kariza berdasarkan pembagian model perilaku politik dalam unit individu aktor politik. Penelitian ini merupakan penelitian kualitatif dengan pendekatan sosiologi sastra. Novel Sophismata karya Alanda Kariza merupakan sumber data primer, adapun berbagai literatur mengenai pendekatan sosiologi sastra digunakan sebagai sumber data sekunder dalam penelitian ini. Teknik pengumpulan data yang digunakan adalah teknik baca dan catat. Sedangkan untuk analisis hasil menggunakan teknik analisis spiral oleh Creswell dengan langkah: manajemen data, pembacaan dan memoing, klasifikasi dan penafsiran serta visualisasi data. Adapun hasil dari penelitian ini, didapati bahwa: tiga tokoh utama dalam novel Sophismata menggambarkan pembagian model prilaku politik pada unit individu aktor politik. Tokoh Johar Sancoyo menggambarkan aktor politik (pemimpin), tokoh Timur menggambarkan aktivis politik dan tokoh Sigi menggambarkan warga negara biasa. Selain itu, dijumpai juga adanya perbedaan pemahaman mengenai politik. Bagi Johar, politik berbicara mengenai kepentingan bersama, sedangkan bagi Sigi politik itu berbicara mengenai kepentingan pribadi yang dibungkus kepentingan bersama.